Simultaneous enhancement of light absorption and improved charge collection in PTB7-Th: PC70BM organic solar cells. (6th March 2017) - Borse, Kunal; Sharma, Ramakant; Gupta, Dipti; Yella, Aswani
ABSTRACT: Enhancing the light absorption and improving the charge collection are considered as two major prerequisite for achieving highly efficient bulk heterojunction organic solar cells (BHJ OSCs). In the present study, we have explored Ga doped ZnO as an electron transport layer for improving the charge collection in one of the promising donor: acceptor system comprised of Poly[4, 8-bis(5-(2-ethylhexyl)thiophen-2-yl)benzo[1, 2-b;4, 5-b']dithiophene-2, 6-diyl-alt-(4-(2-ethylhexyl)-3-fluorothieno[3, 4-b]thiophene-)-2-carboxylate-2-6-diyl)] (PTB7-Th):phenyl-C71-butyric acid methyl ester (PC70BM). With the inverted geometry having a configuration of ITO/GZO (40nm)/PTB7-Th: PC70 BM (100nm)/MoO3 (10nm)/Ag (100nm), maximum power conversion efficiency (PCE) of 7.24% has been achieved, while it is limited at 6.89% for devices with undoped ZnO.It was found that PCE can be further improved to 8.35 % after V-grooved textured PDMS films were attached to the backside of OSC substrates. We attribute this performance enhancement in OSCs is due to increased total optical path length of the incident light within the device.